2009
DOI: 10.5511/plantbiotechnology.26.153
|View full text |Cite
|
Sign up to set email alerts
|

ASN2 is a key enzyme in asparagine biosynthesis under ammonium sufficient conditions

Abstract: The modification and enhancement of plant amino acid accumulation is potentially beneficial in terms of the production of suitable crop plants for food or feeds, and also with respect to possible environmental improvement via the effective use of nitrogen nutrition. It is also expected that modified plants will produce beneficial nitrogenous compounds, such as proteins, secondary metabolites, or nucleic acids. The size of amino acid pools in plants is strictly controlled by certain environmental factors such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this regard, Wong et al () have established a correlation between Atas2 expression and cellular NH 4 + content in Arabidopsis . Furthermore, AS2 has been proposed to be a regulator of Asn biosynthesis and metabolism and as a mediator in the use of N under NH 4 + ‐sufficient conditions in Arabidopsis (Igarashi et al ). Although as genes may play different roles in various aspects of N metabolism (Wong et al ), the poor homology shown between Psas2 and Atas2 (Gaufichon et al ) makes it difficult to correlate the same function to both enzymes, thus meaning that additional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Wong et al () have established a correlation between Atas2 expression and cellular NH 4 + content in Arabidopsis . Furthermore, AS2 has been proposed to be a regulator of Asn biosynthesis and metabolism and as a mediator in the use of N under NH 4 + ‐sufficient conditions in Arabidopsis (Igarashi et al ). Although as genes may play different roles in various aspects of N metabolism (Wong et al ), the poor homology shown between Psas2 and Atas2 (Gaufichon et al ) makes it difficult to correlate the same function to both enzymes, thus meaning that additional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The ASNS is a key enzyme in the Nmetabolism involved in the hydrolyzation of glutamine to synthesize asparagine, the amino acid with the highest N/C ratio, used as the main stored and transported N form through the vascular tissues in many plants (Lea et al, 2007;Gaufichon et al, 2010;Gaufichon et al, 2013). The ASNS overexpression in Arabidopsis revealed a higher asparagine level in plant tissues together with an increased tolerance to N-deprivation (Lam et al, 2003;Igarashi et al, 2009), suggesting that this may be a good and viable strategy for improving NUE. Accordingly, our results suggested that RO showed a faster induction of these genes after initial downregulation compared to UC82, allowing RO to better withstand N-deficiency.…”
Section: Co-expression Network Analysis Reveals N Responsive Modulesmentioning
confidence: 99%
“…AtASN1 and AtASN3 showed quite different expression patterns compared with AtASN2 , and these genes are induced by quite different stimuli [15]. The analysis of ASN mutants indicated that AtASN2 plays a role in the primary N assimilation for N storage and export [16,17]. Decades ago, asparagine synthetase was analyzed in rice, and the expression pattern and function were investigated [18,19].…”
Section: Introductionmentioning
confidence: 99%